COMPLIMENTS GIVEN BY A TEACHER IN SYMPHPNIA MUSIC SCHOOL SURABAYA TO HIGH-, MID-, AND LOW-ABILITY STUDENTS - Jesslin Susilo; Aylanda Dwi-Nugroho (Institute of Research and Community Outreach - Petra Christian University, 2013)
This research aimed at observing compliment and non-compliment feedbacks between a teacher at a private music school and her students who had different abilities. The data were the recorded piano lesson of each student and the analysis was focused on the compliments and exchange structures as directed by Holmes (1988) and Coulthart (1992). The findings showed that all students received more compliments than non-compliments. For the compliment, all types of student received ‘Good’ token the most. On the second place high-ability student received ‘Very Good’, while mid- and low-ability student got mitigation. As for the non-compliment feedback, high- and low-ability student got criticism the most and it was found that the frequency of no feedback in mid-ability student occured the most.